Risk Factors for Progression of Chronic Kidney Disease With Glomerular Etiology in Hospitalized Children - He, Guohua; Li, Chenglong; Zhong, Xuhui; Wang, Fang; Wang, Haibo; Shi, Ying; Gan, Lanxia; Ding, Jie (Frontiers in Pediatrics, 2021)
Aim To Identify association between risk factors to Chronic kidney disease (CKD) stage 5 in children with glomerular diseases in children in China. Methods The Hospital Quality Monitoring System database was used to extract data for the study cohort. The primary outcome included progression to CKD stage 5 or dialysis. Cox regression was used to assess potential risk factors. Patients with lower stages (CKD stage 1 and 2) and higher stages (CKD stage 3 and 4) at baseline were analyzed separately. Results Of 819 patients (4089 hospitalization records), 172 (21.0%) patients reached the primary outcome during a median followed-up of 11.4 months. In the lower stages group, factors associated with the primary outcome included older age (Hazard Ratio [HR], 1.21; 95% confidence interval [CI], 1.10–1.34) and out-of-pocket payment (HR, 4.14; 95% CI, 1.57–10.95). In the higher stages group, factors associated with the primary outcome included CKD stage 4 (HR, 2.31; 95% CI, 1.48–3.62) and hypertension (HR, 1.99; 95% CI, 1.29–3.07). The medical migration rate was 38.2% in this study population. Conclusion There are different risk factors for progression to the primary outcome in different stages in CKD with glomerular etiology. Further prospective studies are needed to assess these risk factors. The high medical migration rate reflected the regional disparities in the accessibility of pediatric kidney care between regions.